Reductions in Hard Drug Use Among Homeless Youth Receiving a Strength-Based Outreach Intervention: Comparing the Long-Term Effects of Shelter Linkage Versus Drop-in Center Linkage. (7th June 2017) - Guo, Xiamei; Slesnick, Natasha
ABSTRACT: Objectives: The current study sought to test hard drug use outcomes for youth receiving a strengths-based outreach and advocacy intervention that linked youth to either a shelter or a drop-in center. Methods: Homeless youth (14–24 years old) were engaged by research assistants (RAs) at soup kitchens, parks, libraries, and other locations that homeless youth were known to frequent. Youth were randomly assigned to receive six months of advocacy that focused on linking youth to a drop-in center ( n = 40) or to a crisis shelter ( n = 39). Follow-up assessments were conducted at 3, 6, and 9 months post-baseline. Hard drug use over time was the main outcome. Intervention condition and service connection were used as predictors for the baseline level and the slope of change in hard drug use over time. Data analysis was conducted with Bernoulli Hierarchical Generalized Linear Modeling in HLM7. Results: The current study found that those who were in the drop-in linkage condition exhibited a greater reduction in their odds of using hard drugs during the follow-up points than their counterparts in the shelter linkage condition. And finally, those who utilized services more often during the follow-ups were those who exhibited less hard drug use at baseline and less reduction in their odds of using hard drugs. Conclusions: This study suggests that drop-in centers, which are often characterized by low-demand programming and few behavioral restrictions, are effective for addressing hard drug use among homeless youth.